2000
DOI: 10.1038/78496
|View full text |Cite
|
Sign up to set email alerts
|

High-performance affinity beads for identifying drug receptors

Abstract: We have developed a method using novel latex beads for rapid identification of drug receptors using affinity purification. Composed of a glycidylmethacrylate (GMA) and styrene copolymer core with a GMA polymer surface, the beads minimize nonspecific protein binding and maximize purification efficiency. We demonstrated their performance by efficiently purifying FK506-binding protein using FK506-conjugated beads, and found that the amount of material needed was significantly reduced compared with previous method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
219
1
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(227 citation statements)
references
References 18 publications
3
219
1
4
Order By: Relevance
“…36 NF-kB activity was found to be a redox regulated by and dependent on APE1. 13 Our data showed irradiation-induced activation of NF-kB. NF-kB has been linked to radioresistance in CRC cells, 14 and inhibition of NF-kB sensitizes CT26 CRC cells to ionizing radiation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…36 NF-kB activity was found to be a redox regulated by and dependent on APE1. 13 Our data showed irradiation-induced activation of NF-kB. NF-kB has been linked to radioresistance in CRC cells, 14 and inhibition of NF-kB sensitizes CT26 CRC cells to ionizing radiation.…”
Section: Discussionmentioning
confidence: 56%
“…12 In addition to its DNA repair functions, APE1, also called redox factor-1, participates in other crucial cellular processes, including the response to oxidative stress, regulation of transcription factors, including nuclear factor kB (NF-kB). 13 NF-kB has been shown to be associated with radioresistance in CRC cells. 14 Therefore, as a bifunctional AP endonuclease/redox factor, APE1 may be associated with constitutive and induced radioresistance.…”
Section: Introductionmentioning
confidence: 99%
“…E3330 had previously been shown to suppress NF-jB transactivational activity, and, in doing so, to promote an anti-inflammatory state, exhibiting potential utility in the treatment of various forms of hepatitis [(80) and references therein]. The APE1-E3330 interaction was validated using multiple biochemical and biological approaches, and was determined to have an apparent binding constant of 1.6 nM by surface plasmon resonance (191). Since this discovery, the ability of E3330 to selectively inactivate the redox activity of APE1 and suppress the activity of several transcription factor targets has been confirmed in multiple studies [reviewed in Kelley et al (101)].…”
Section: Small-molecule Inhibitorsmentioning
confidence: 99%
“…The design of APE1 redox inhibitors has been more limited, presumably due to the lack of a high-throughput screening assay to identify molecules that inactivate the redox function of the protein. Nevertheless, using a bead-based approach and nuclear cell extracts, Shimizu et al (191) identified APE1 as a major binding protein for the quinone derivative, E3330 (introduced in ''APE1 Biological Roles'' section). E3330 had previously been shown to suppress NF-jB transactivational activity, and, in doing so, to promote an anti-inflammatory state, exhibiting potential utility in the treatment of various forms of hepatitis [(80) and references therein].…”
Section: Small-molecule Inhibitorsmentioning
confidence: 99%
“…In the current study, we focused on AAVS1 and searched for proteins that bind to the core elements of AAVS1. Towards this end, we carried out affinity chromatography using latex beads to which one can conjugate various biologically active components, such as chemical compounds (26), nucleic acids (30), and proteins (9). In a one-step affinity chromatography procedure, we purified TRP-185, a 185-kDa protein previously implicated in the activation of human immunodeficiency virus type 1 gene expression (33), from HeLa cell nuclear extracts (NE).…”
mentioning
confidence: 99%